Marginalization of Women in Marriage: A Study of Shashi Deshpande’s The Dark Holds No Terrors and That Long Silence (Literary Voice, 2024)
Marginalization in society is not confined to limitations of opportunities to grow independently and lack means of endurance. It refers to the creation of an environment in which the individual is made to feel pride even in slavery. Marginalization in the case of women is more pronounced as it is not limited to any caste, creed or religion. It is a universal phenomenon and marriage as an institution is one of the basic foundations on which the marginalization of women is culturally strengthened. Marriages are a pivotal part of every society. By conforming to the institution of marriage, two distinct minds take oaths to stick by each other’s side lifelong. But in reality, the institution of marriage replicates the other side of patriarchal domination which contributes to the peripheral status of women. They are subjected to inevitable suppression, subjugation, and oppression in the environs of the marital frame regardless of the renunciation and forsaking of individuality by the woman for the sake of family. They are the victim of sheer oppression and violence due to their vulnerable status from time immemorial. In this paper, an attempt has been made to bring forth the hardships of marital life and how it assists in the marginalization of women with reference to the works of Shashi Deshpande. Her works of fiction, The Dark Holds No Terrors (1980) and That Long Silence (1988) aptly elucidate the issues of marital discord and disharmonious conjugal relationships which career-oriented women experience in their day-to-day existence. Women helplessly oscillate between traditional codes and modern aspirations, bearing the pangs of dead desires and unexpressed thoughts in public as well as domestic spheres. Characterization of women like Sarita and Jaya delineate the marginalization of women in a poignant and powerful manner.
Keywords: marriage, marginalization, patriarchy, discrimination, women, marital discords.